The β20–β21 of gp120 is a regulatory switch for HIV-1 Env conformational transitions. Issue 1 (December 2017) - Herschhorn, Alon; Gu, Christopher; Moraca, Francesca; Ma, Xiaochu; Farrell, Mark; Smith, Amos; Pancera, Marie; Kwong, Peter; Schön, Arne; Freire, Ernesto; Abrams, Cameron; Blanchard, Scott; et al.
Abstract The entry of HIV-1 into target cells is mediated by the viral envelope glycoproteins (Env). Binding to the CD4 receptor triggers a cascade of conformational changes in distant domains that move Env from a functionally "closed" State 1 to more "open" conformations, but the molecular mechanisms underlying allosteric regulation of these transitions are still elusive. Here, we develop chemical probes that block CD4-induced conformational changes in Env and use them to identify a potential control switch for Env structural rearrangements. We identify the gp120 β20–β21 element as a major regulator of Env transitions. Several amino acid changes in the β20–β21 base lead to open Env conformations, recapitulating the structural changes induced by CD4 binding. These HIV-1 mutants require less CD4 to infect cells and are relatively resistant to State 1-preferring broadly neutralizing antibodies. These data provide insights into the molecular mechanism and vulnerability of HIV-1 entry. Binding of viral envelope glycoproteins (Env) to the host cell CD4 receptor mediates HIV-1 entry. Here, the authors develop compounds that inhibit the CD4-induced conformational changes in Env and show that the gp120 β20-β21 element is a key regulator for Env transitions.